Subjective well-being and educational performance in PISA: A copula based approach - Baldwin Tong (Social Sciences and Humanities Open)
The relationship between education and subjective well-being has been a topic of interest for researchers and educators alike. In this paper, we aim to explore the intricate interplay between educational performance and subjective well-being, conducting a copula-based analysis of the PISA 2022 dataset while using factor analysis to construct a novel multi-dimensional subjective well-being measure.Copulas provide a flexible framework for the modeling of multivariate dependencies while allowing for the independent consideration of marginal distributions. This approach can provide more nuanced analysis of variables under observation. The results of the analysis indicate that there is a weak relationship between educational performance on the PISA assessment and subjective well-being.These findings have important implications for educators and policymakers, as they suggest that efforts to improve educational performance and subjective well-being simultaneously may not be successful. Additionally, the study highlights the relatively weak relationship between educational performance and life satisfaction among adolescents.